THE INFLUENCE OF TRAINING AND DEVELOPMENT TO EMPLOYEE PERFORMANCE - Pebrida Saputri; Devia Lorensa; Asriani Asriani; Salda Zainurossalamia ZA (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Training and development have an important role to improve employee performance to improve higher quality human resources . The purpose of this study is to find out the role of training and development on the performance of analysis consultant employees on environmental impacts (AMDAL) . Hypothesis training and pegembangan are significantly affecting AMDAL consultant employee performance. The population in the study this is all the employees who have followed the training and development ka ryawan as many as 35 people. Mechanical taking samples in research this is purposive sampling The method that is used in research this is the collection of data through questionnaires, the study literature, and observation. The technique used to analyze simple linear regression data and examine hypotheses simultaneously and partially. The result is that training and development significantly influence employee performance simultaneously.